Isolation-Amplification of ENV-TM Subunit Genes of Jembrana Disease Virus by a Single Step RT-PCR and Its Direct Cloning in PCR2.1-TOPO Plasmid - Asmarani Kusumawati; Basuki Hidayat; B. Sardjono; Joannes Sri Widada (Faculty of Animal Science, Universitas Gadjah Mada, 2003)
Artikel dalam bentuk PDF